2015
DOI: 10.1126/scitranslmed.aaa2384
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative brain cancer detection with Raman spectroscopy in humans

Abstract: Cancers are often impossible to visually distinguish from normal tissue. This is critical for brain cancer where residual invasive cancer cells frequently remain after surgery, leading to disease recurrence and a negative impact on overall survival. No preoperative or intraoperative technology exists to identify all cancer cells that have invaded normal brain. To address this problem, we developed a handheld contact Raman spectroscopy probe technique for live, local detection of cancer cells in the human brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
496
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 535 publications
(500 citation statements)
references
References 48 publications
3
496
0
1
Order By: Relevance
“…In vivo RS has been shown to be a highly specific and sensitive cancer detection method for multiple pathologies with detection accuracy values usually limited to approximately 90% (7,(15)(16)(17)30), while oncology applications using IFS and/or DRS have been similarly limited (26,28,29,31). We hypothesized that IFS and DRS have the potential to synergistically complement the molecular information provided by RS to maximize cancer detection capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo RS has been shown to be a highly specific and sensitive cancer detection method for multiple pathologies with detection accuracy values usually limited to approximately 90% (7,(15)(16)(17)30), while oncology applications using IFS and/or DRS have been similarly limited (26,28,29,31). We hypothesized that IFS and DRS have the potential to synergistically complement the molecular information provided by RS to maximize cancer detection capability.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown dramatic survival advantages by surgically minimizing the volume of cancers, including melanoma (1), brain (2), breast (3), and lung cancers (4). Otherwise, precancerous, cancerous, or normal tissue invaded by cancer cells remain (5)(6)(7). When these residual cells are not eradicated by adjuvant treatments, they give rise to recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Additional information can be obtained by positron emission tomography, functional MRI, diffusion weighted imaging, fluid-attenuated inversion recovery, and magnetic resonance spectroscopic imaging (MRSI). Raman spectroscopy performed in vivo seeks to provide chemical information that allows rapid identification of cancerous tissue (14). Fluorescence imaging uses appropriate molecular labels to visualize tumors during surgery (15,16).…”
mentioning
confidence: 99%
“…Raman spectroscopy and imaging has, through its ability to identify subtle changes in tissue composition, found applications in the fields of early-stage inflammatory apoptosis of adult hippocampal stem cells (Ladiwala et al 2014), cancer identification in human brain tissue (Jermyn et al 2015;Ji et al 2013) and changes in blood vessels associated with heart disease (Matthaus et al 2012). …”
Section: Raman Spectroscopymentioning
confidence: 99%